2018
DOI: 10.1001/jama.2018.12328
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits and Risks of High-Nicotine e-Cigarettes

Abstract: The substantial reduction in smoking in the United States represents one of the most important public health advances of the last 50 years. Among children and adolescents this progress has been particularly encouraging, with smoking rates declining among 8th-, 10th-, and 12th-grade students from 28.3% in 1997 to 5.4% in 2017. 1 These positive trends suggest that the powerful appeal of tobacco and nicotine has been reduced in younger generations. However, emerging products such as JUUL, Suorin Air, Envii FITT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…33 In an encouraging first step to stem use among youths, the FDA reported that it would invoke the regulatory mechanism needed to remove flavored e-cigarettes from the market. 4 We believe the FDA, however, can and should do much more. The 2017 delay by the FDA to enforce its authority to regulate e-cigarettes and require premarket review created the opportunity for JUUL to enter and dominate the marketplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In an encouraging first step to stem use among youths, the FDA reported that it would invoke the regulatory mechanism needed to remove flavored e-cigarettes from the market. 4 We believe the FDA, however, can and should do much more. The 2017 delay by the FDA to enforce its authority to regulate e-cigarettes and require premarket review created the opportunity for JUUL to enter and dominate the marketplace.…”
Section: Discussionmentioning
confidence: 99%
“…Given that nearly all e-cigarettes contain nicotine, 1 public health officials worry that rates of addiction to tobacco and other drugs will increase in young people, as early nicotine exposure can harm the brain and increase addiction susceptibility. [2][3][4] A substantial body of evidence shows an association between e-cigarette use and future combustible tobacco use, with some research suggesting that young adult e-cigarette users are 4 times more likely to smoke cigarettes within 18 months compared with their nicotine-naive peers. 5,6 In addition, recent vaping-related illnesses reported by more than 2000 individuals have led to 39 deaths.…”
mentioning
confidence: 99%
“…Parents of participating youth and youth provided written permission and assent, respectively. We focus on the most recent wave of data collection (December 2016 to January 2018), given the recent proliferation of high-nicotine delivery devices . The sample included adolescents aged 12 to 17 years who had vaped more than once in their lifetime and at least once in the past 30 days (ie, current vapers), weighted to be representative of all US adolescents who vape.…”
Section: Methodsmentioning
confidence: 99%
“…USB-like e-cigarettes, and one product in particular, Juul, has captured over 75% of the market share of the e-cigarette category since its introduction in 2014–2015. This product transformed both the category and use patterns given its efficient delivery of highly concentrated nicotine, flavors, and covert design [14,15,16]. The increasing use of e-cigarettes among youth threatens five decades of public health gains in successfully deglamorizing, restricting, and decreasing the use of tobacco products [17].…”
Section: E-cigarettes: An Epidemic and A Threat To Public Healthmentioning
confidence: 99%